PENGARUH MODEL PEMBELAJARAN ARIAS DAN BAKAT NUMERIK TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Anak Agung Ayu Manik Arini; I Wayan Eka Mahendra (FPMIPA IKIP PGRI Bali, 2016)
The Effect of Learning Model Arias and Numerical Aptitude Toward Mathematical Concept Comprehension of Students Based on the analysis of data was obtained (1) There are differences in the understanding of mathematical concepts among students who follow ARIAS learning model with learners who followed the conventional learning model class VIII SMP Negeri 3 Tembuku year 2015/2016 . (2) There is an interaction between the learner and the learning model ARIAS numerical aptitude of students to the students’ comprehension of math concepts in class VIII SMP Negeri 3 Tembuku year 2015/2016. (3) There are differences in student’s comprehension of mathematical concepts that have a high numerical aptitude among students who follow ARIAS learning model with learners who followed the conventional learning models in academic year 2015/2016. (4) There is no difference in the student’s comprehension of mathematical concepts that have a low numerical aptitude among students who follow ARIAS learning model with learners who followed the conventional learning models in academic year 2015/2016.